Implementación de pilares del TPM en la empresa Zollner Electronics Costa Rica Ltda - Blanco-Calvo, Esteban Manuel (Instituto Tecnológico de Costa Rica, 2017)
The maintenance management in the companies should be involved on the reduction of losses, wastes and breakdowns so that together with other areas, they progress towards a lean manufacturing company as Zollner Electronics Costa Rica Ltd. intends to be. To achieve that, one of the bases is the total productive maintenance (TPM), with which it is sought to increase indices of efficiency, availability and quality. To do this, the project starts with the application of 5S (an important key for TPM implementation) both in the maintenance department and in the production lines of the SMT area. Subsequently, autonomous maintenance and focused improvements are introduced as initial pillars. For the former, manuals are made and implemented for the most critical machines in the production process. For the focused improvements, signaling is placed on the compressed air inlet gauges to the machines and the cleaning activities have been strengthening for sensors and nozzles which have presented considerable errors in the past. To complement and improve the maintenance management, it has been made a codification for the equipment, the criticality has been defined and the maintenance work orders have been introduced, while the department's digital information system has been improved. It is sought to measure the improvements and analysis of the impact of the maintenance on the company, so it is implemented maintenance indexes such as TMEF, TMDR, reliability and availability. For the latter, improvements of 2% are evident at the end of the project. There is also measured the overall efficiency index for which there is a 21% increase between January and May 2017. In addition, a strategy of cultural change is designed to give continuity and sustainability to the project within the company.

Dentro de la gestión del mantenimiento en las empresas, debe buscarse la reducción de pérdidas, desperdicios y averías para que en conjunto con otras áreas se avance hacia una compañía de manufactura esbelta como lo pretende ser Zollner Electronics Costa Rica Ltda. Para llegar a ello una de las bases es el mantenimiento productivo total (TPM), con el cual se buscan aumentar índices de eficiencia, disponibilidad y calidad. Para ello, se inicia con la aplicación de las 5S, herramienta clave para la implementación del TPM, tanto en el departamento de mantenimiento como en las líneas de producción del área de SMT. Posteriormente, se introduce el mantenimiento autónomo y las mejoras enfocadas como pilares iniciales. Para el primero se realizan y se implementan manuales para las máquinas más críticas del proceso productivo. Para las mejoras enfocadas se coloca señalización en los manómetros de entrada de aire comprimido a las máquinas y se fortalecen actividades de limpieza de sensores y boquillas los cuales han presentado errores considerables en el pasado. Para complementar y mejorar la gestión del mantenimiento se implementa la codificación de equipos, la criticidad de los mismos y se introducen las órdenes de trabajo de mantenimiento, a la vez que se mejora el sistema de información digital del departamento. Se busca la medición de las mejoras y el análisis del impacto del mantenimiento en la empresa, por lo que se implementan índices de mantenimiento como el TMEF, TMDR, la confiabilidad y la disponibilidad. Para este último se evidencian mejorías de un 2% al finalizar el proyecto. Se da la medición del índice de eficiencia global para el cual se da un aumento de 21% entre enero y mayo de 2017. Además, se diseña una estrategia de cambio cultural para dar continuidad y sostenibilidad al proyecto dentro de la empresa.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Mantenimiento productivo; Gestión; Eficiencia; Montaje superficial; Tecnología